Global marketing : concepts, strategies, practice : text and readings - Akhter, Syed H. (Cincinnati, OH : South-Western College, 1995)
Global marketing. The economic environment. The financial environment. The political and legal environment. The cultural environment. Global product strategies. Global pricing decisions...
Keywords: Marketing; Export marketing; Export marketing